The Discursive Construction of Strategists' Subjectivities: Towards a Paradox Lens on Strategy - Dameron, Stéphanie; Torset, Christophe (Journal of Management Studies, 2014)
AbstractUntil recently, the field of strategy has neglected the question of what it means to be a strategist. Based on an analysis of 68 interviews with strategy practitioners, our results highlight four main tensions that emerge from strategists' discourses on strategizing work: the social tension, the cognitive tension, the focus tension, and the time tension. This tension‐based representation of strategy enables us to differentiate between three forms of strategists' subjectivities, i.e. the ways by which strategists discursively cope with tensions as a means of constituting their identity and legitimacy: the mythicizing subjectivity, the concretizing subjectivity, and the dialogizing subjectivity. Such results shed light on what a strategist is, suggesting that strategizing can be conceptualized as the art of balancing tensions and that multiple strategists' subjectivities within a paradox lens on strategy may in fact co‐exist.